An iconographical study of the works of the Meidas painter and his associates - Burn, L; Burn, Lucilla (1982)
﻿ The Introduction surveys previous work on the Meidias Painter and his Associates, and outlines the form that the present study is to take. In Chapter I the Painter and his Associates are introduced; their style is briefly assessed, and an attempt is made to establish their dates and their artistic, social and historical background. In the following Chapters, the Meidian scenes are grouped together by subject and mood. Each group of scenes is similarly treated; the representations are first described and then discussed. Reference is made to the literary and artistic traditions behind each subject, and attempts are made to account for any unusual or especially interesting features of the scenes, and to determine the factors which influenced their design. In Chapter II the more violent scenes are discussed, the Amazon-, gigant- and centauromachies, the Minotaur, Persians chasing women and Oedipus slaying the sphinx. Chapters III and IV discuss the 'heavenly garden' scenes which are most characteristic of the Meidian group, scenes set in paradise gardens from which all violence is excluded. In these Chapters the Meidias Painter's name vase and related scenes, Phaon and Adonis, Thamyris, Marsyas and Mousaios, Personifications, Chryse, Apollo and Artemis, Asklepios, Eleusinians, Dionysos and Aphrodite are all discussed. Chapter V is reserved for non-violent yet non-heavenly garden scenes - Nausikaa, Amymone, Ixion and Trojan themes. Chapter VI deals with non-mythological scenes, those of women and cult. In the Conclusion it is suggested that the two major characteristics of Meidian iconography are its interest in nature and its concern to soften and romanticize mythology, and it is argued that both may derive from the contemporary social and political climate. A catalogue of vases attributable to the Meidias Painter and his Associates is appended.